Culpa in contrahendo: from the historical perspective to the challenges of the new industrial revolution. A look at the basic regulations (1215/2012 and 864/2007) and their link with the new pre-contractual dispute resolution mechanisms - Martínez Ortiz, Pedro José (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Starting from the reality of the diffuse concept that –even today– is culpa in contrahendo –especially in the area of jurisdiction with a foreign element, but also, although less so, in the area of applicable law–, the hypotheses of the sufficiency or insufficiency of the mechanisms that regulate it –explicitly or implicitly– in the face of the challenges of the new industrial revolution are posed. This revolution, conveyed through contractual legal realities such as ‘smart contracts or artificial intelligence, poses a great challenge when it comes to protecting due diligence in the ‘iter contractus’. Moreover, it adds a component of greater complexity: there is no longer only one foreign element that governs the relations between parties –the basis of international law–, but the challenge is global and its growth -due to technological change- is exponential.
Keywords: culpa in contrahendo; jurisdiction; applicable law; industrial revolution; smart contracts; artificial intelligence